2020
DOI: 10.1016/j.bja.2020.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of sugammadex or neostigmine for reversal of neuromuscular block on the incidence of pulmonary complications in older adults undergoing prolonged surgery

Abstract: Background: Residual neuromuscular block has been associated with postoperative pulmonary complications. We hypothesised that sugammadex reduces postoperative pulmonary complications in patients aged !70 yr having surgery !3 h, compared with neostigmine. Methods: Patients were enrolled in an open-label, assessor-blinded, randomised, controlled trial. At surgical closure, subjects were equally randomised to receive sugammadex 2 mg kg À1 or neostigmine 0.07 mg kg À1 (maximum 5 mg) for rocuronium reversal. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
122
2
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(133 citation statements)
references
References 38 publications
3
122
2
6
Order By: Relevance
“…In a protective ventilation group, the incidence of pneumonia was demonstrated by 1 study to be lower than that for a conventional-ventilation group, although the difference was not signi cant. [40] In our investigation, most of the ventilation parameters followed the lung-protective strategy; the mean tidal volume in both the PPC and non-PPC groups was almost 9 mL/kg, and all parameters of the groups were not statistically different. As to the anesthetic-risk factors, no relationship was apparent between the PPCs and airway equipment, inhalation agent, or anesthetic technique.…”
Section: Intraoperative and Postoperative Parametersmentioning
confidence: 51%
See 1 more Smart Citation
“…In a protective ventilation group, the incidence of pneumonia was demonstrated by 1 study to be lower than that for a conventional-ventilation group, although the difference was not signi cant. [40] In our investigation, most of the ventilation parameters followed the lung-protective strategy; the mean tidal volume in both the PPC and non-PPC groups was almost 9 mL/kg, and all parameters of the groups were not statistically different. As to the anesthetic-risk factors, no relationship was apparent between the PPCs and airway equipment, inhalation agent, or anesthetic technique.…”
Section: Intraoperative and Postoperative Parametersmentioning
confidence: 51%
“…Moreover, there was a threefold increase in the 30-day hospital readmission rate of the neostigmine group (15%) relative to that of the sugammadex group (5%). (40) In recent years, our institution has been revising its perioperative management protocol for enhanced recovery (the Siriraj ERAS Protocol). Our observation has been that perioperative outcomes appear to be improved when a goal-directed therapy is employed as opposed to a liberal uid therapy.…”
Section: Intraoperative and Postoperative Parametersmentioning
confidence: 99%
“…Sugammadex has been proven to be associated with a lower rate of rNMB at the time of extubation and PACU admission, and also be associated with a 40% reduction in r NMB compared with neostigmine. 15 Recently, a multicentre observational matched cohort study showed that sugammadex administration was associated with improvement in pulmonary outcomes compared with neostigmine. 16 We presume that the potential mechanism of sugammadex reducing the incidence of PPCs is that sugammadex may be quicker and more efficient to enhance the recovery of muscle strength in the early postoperative period than neostigmine.…”
Section: Open Accessmentioning
confidence: 99%
“…The possibility of residual neuromuscular blockade (RNMB) after the use of neuromuscular blocking agents has been known for some time. However, in recent years, there has been an increase in the number of publications showing its high incidence, its relationship to postoperative pulmonary complications (POPC), and, therefore, to increase potential healthcare costs [3][4][5][6]. POPC include upper airway obstruction, oxygen desaturation, bronchoaspiration, pneumonia, atelectasis, and reintubation for severe respiratory failure requiring an unplanned admission to an intensive care unit (ICU) [2,3,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies and multiple international organizations have suggested that every patient receiving nondepolarising neuromuscular blocking drugs should have at least qualitative, and preferably quantitative intraoperative monitoring of the neuromuscular blockade (NMB) and assessment of the pharmacologic antagonism of NMB [8][9][10][11]. Nevertheless quantitative measurements of drug-induced NMB and the adequacy of pharmacologic reversal have not been widely utilized by anaesthesia professionals [3][4][5]. The rates of intraoperative neuromuscular monitoring (NMM) vary according to each center and do not cover the entire surgical patients with general anaesthesia and neuromuscular blocking agents [11][12][13].…”
Section: Introductionmentioning
confidence: 99%